The H3 histone chaperone NASPSIM3 escorts CenH3 in Arabidopsis - Le Goff, Samuel; Keçeli, Burcu Nur; Jeřábková, Hana; Heckmann, Stefan; Rutten, Twan; Cotterell, Sylviane; Schubert, Veit; Roitinger, Elisabeth; Mechtler, Karl; Franklin, F Christopher H; Tatout, Christophe; Houben, Andreas; et al. (Plant journal, 2020)
Centromeres define the chromosomal position where kinetochores form to link the chromosome to microtubules during mitosis and meiosis. Centromere identity is determined by incorporation of a specific histone H3 variant termed CenH3. As for other histones, escort and deposition of CenH3 must be ensured by histone chaperones, which handle the non-nucleosomal CenH3 pool and replenish CenH3 chromatin in dividing cells. Here, we show that the Arabidopsis orthologue of the mammalian NUCLEAR AUTOANTIGENIC SPERM PROTEIN (NASP) and Schizosaccharomyces pombe histone chaperone Sim3 is a soluble nuclear protein that binds the histone variant CenH3 and affects its abundance at the centromeres. NASPSIM3 is co-expressed with Arabidopsis CenH3 in dividing cells and binds directly to both the N-terminal tail and the histone fold domain of non-nucleosomal CenH3. Reduced NASPSIM3 expression negatively affects CenH3 deposition, identifying NASPSIM3 as a CenH3 histone chaperone.
Keywords: histony; Arabidopsis; proteiny huseníčku; kinetochory; Histones; Centromere; Arabidopsis Proteins; Kinetochores; Schizosaccharomyces; centromera